Legends of Students’ "Clever Answers": Criticism or Affirmation of the Educational System? - Jana Baćević (University of Belgrade, 2016)
This paper represents an analysis of a group of urban legends from US universities, gathered from a number of web sites and in certain cases compared with analogous examples from Serbia. These legends concentrate around the motif of "clever answers", in which students use witty or otherwise unconventional means to solve problems or answer questions during exams or other forms of knowledge examination, and usually end up being rewarded for their creativity. The analysis of the formal structure of these legends, as well as their possible functions, indicates that, on the one hand, legends of "clever answers" can represent a form of criticism of the higher education system, but on the other actually aid its reproduction and reinforce its role in the social order. Finally, the implications of this interpretation are investigated in the context of contemporary global transformations of higher education.